Images of Islam and Administration in British Baluchistan during the Sandeman System: From Post British Occupation till Inception of Islamic Republic of Pakistan (Al-Qamar, 2019)
The present article will acquaint an analytical review of the Sandeman system and its impacts on the inhabitants and religion of Baluchistan from 1877 to 1947. Sir Robert Groves Sandeman was a British Indian Army officer and colonial administrator. Sandeman was acknowledged for his specific behavior in Baluchistan, where he innovated the prevailing political and social order of "tribal mollification and counterinsurgency" that faced and withstand with courage up to the emergence of Pakistan in 1947. He had shown great respect for Islam and contributed to the systematic teaching of Islamic knowledge in all tiers of education. In fact, instead of promoting missionaries, he had helped Islam to progress. With the assistance of Nawāb Sir Imām Bukhsh Khān Mazzārī in 1876, he discussed the terms of arrangement and developed the significant Treaty of Qalāt along with the Khān of Qalāt. In 1877, he appointed agent to the governor-general of Baluchistan. He acquainted ahead of the time system for the counter-insurgency of Baluchistan tribes. Terminologically this system of counterinsurgency of Baluchistan tribes is acknowledged as ‘Sandemanization’, which was implemented on the Baluchistan tribes in 1877 and ended on the independence of India in 1947. He had introduced educational reforms too through this system with no intention to intervene in the Islamic outlook of the province neither he tries to make Baluchistan a Christian identity.
Keywords: Baluchistan; Islam; administration; British; Sandeman